PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER ISLAMI PESERTA DIDIK DI SMPN 1 KARAWANG - Neng Nila Nursafaat; Rebi Hadinata; Muhlis Imzani Taman Najib; Agus Fudholi; Ajat Sudarajat (STKIP Subang, 2026)
Education plays a vital role in shaping students' character. In the school environment, the development of Islamic character is carried out through collaboration between teachers and the school community by integrating religious values into various activities. Education is not only focused on transferring knowledge but must also instill faith, build character, and develop students' potential according to religious teachings, particularly the Qur'an for Muslims. Islamic character encompasses responsibility, honesty, independence, discipline, and mutual respect. This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping students' Islamic character at SMPN 1 Karawang. This qualitative descriptive research was conducted on August 7, 2024. The results show that PAI teachers act as mentors, educators, and motivators. As mentors, they foster positive habits through habituation methods, such as congregational prayers and Quranic recitation activities. As educators, they serve as role models by demonstrating Islamic attitudes and behavior. As motivators, they encourage students to learn, maintain worship practices, and optimize their potential. Effective development of Islamic character can help students become individuals with noble morals both in school, family, and society. However, observations indicate ongoing challenges in implementing Islamic character, such as a lack of politeness and self-confidence. Therefore, strengthening the role of PAI teachers is crucial to nurturing a generation with strong Islamic character and integrity.